Nutritional Status and Some Eating Habits of Children with Peptic Ulcers at Vietnam National Children’s Hospital - Mai, Chu Thi Phuong; Thi Mai, Nguyen; Anh Tho, Pham; Manh Kien, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1DO - 10.25073/2588-1132/vnumps.4642, 2025)
Peptic ulcer disease is a common gastrointestinal disorder. A cross-sectional study followed by a prospective study involving 124 children aged 10-14 diagnosed with peptic ulcer disease at the National Children's Hospital from January 2023 to December 2023 aimed to assess the nutritional status and describe the actual dietary intake of the children. Most of the 124 children included in the study were boys (85.5%). According to the BMI/age index, 9.7% of the children were malnourished and underweight, and 25.9% were overweight or obese. Additionally, 8.1% of the children were stunted. The energy intake and the nutrients including protein, lipids, and carbohydrates met the recommended requirements for age and gender. However, the proportion of children consuming inappropriate foods for peptic ulcer disease was still high, with over 90% consuming sweets, fast food, and fried food, and 75.8% consuming spicy food. Therefore, children with peptic ulcer disease should be assessed for nutritional status and receive dietary counseling to ensure appropriate dietary habits and food choices.